Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Terhadap Hasil Belajar Siswa SMP Negeri 11 Halmahera Tengah - Iksan B. Aly; Rafika Fakir (Jurnal Ilmiah Wahana Pendidikan, 2022)
STAD is the simplest cooperative learning and the most appropriate for teachers and students who are just trying cooperative learning. STAD's cooperative idea is to motivate students to support and help each other in mastering the subject matter. Students are accustomed to supporting each other and their teammates to do their best and show the norm that learning is important. According to Zakaria and Ikhsan (2007) cooperative learning is based on the assumption that learning will be meaningful if students actively cooperate and share ideas with other students in solving problems. The STAD learning strategy has the potential to improve student learning outcomes. Biology learning outcomes that are expected in the learning process are students have a certain competence that includes the cognitive, affective, and psychomotor domains. Learning outcomes cannot be separated from the competencies possessed by students in understanding the concepts being studied as a basis for teachers when students have reached the KKM set by students, they are said to be complete in learning the concepts that have been studied. Based on the results of limited observations and interviews with biology teachers at SMP Negeri 11 Halmahera Tengah, where biology teachers provide information that student learning outcomes are still low, the acquisition rate is still below the 65% KKM on the topic of the human respiratory system so that teachers try to improve by applying appropriate learning models. improve students' KKM scores and assist students in understanding concepts together which will later improve their learning outcomes. Based on the results of data analysis and discussion, it can be concluded that there is an effect of the Student Team Achievement Division (STAD) learning model on student learning outcomes at SMP Negeri 11, Central Halmahera district, seen from the results of the ANOVA test at a significance value of 0.000 0.05 or sig 0.05.